Cloud-Capped Towers: Capturing Terrain Characteristics Using Topographic Functionals - Earl, Edward; Metzler, David (Quaestiones Geographicae, 2015)
We introduce three related mathematical measures of terrain based on a particularly elegant combination of relief and steepness, which we term omnidirectional relief and steepness (ORS). One measure, reduced ORS (RORS), is particularly suited to creating lists of notable features, and another, domain relief and steepness (DRS), measures the ruggedness of a region.